Osteogenic Differentiated Human Bone Marrow Stem Cells Contribute to Sprouting Angiogenesis Deceleration via Paracrine Excreted IGFBP7 - Shiyu Sun; Cen Cao; Yaru Guo; Yi Hou; Yanze Meng; Yuman Li; Feng Mei; Zhewen Hu; Yao Li; Yuting Niu; Yiming Chen; Lili Chen; et al. (Advanced Materials Interfaces)
Abstract Deceleration of sprouting angiogenesis until its final disappearance after blood vessel reconstruction is crucial for controlled tissue repair; however, its underlying mechanism remains unclear. It is reported that osteogenic differentiated bone marrow stem cells (OD‐BMSCs) contribute to sprouting angiogenesis deceleration by releasing intrinsic “OFF” signals. In vitro experiments show that insulin‐like growth factor‐binding protein 7 (IGFBP7) is the main component of OD‐BMSCs paracrine products which could inhibit the tube formation ability of endothelial cells. In addition, cell functional experiments show that IGFBP7 inhibits sprouting angiogenesis by reducing cell migration and tip cell specification. Furthermore, it is found that early IGFBP7 intervention, which accelerates sprouting angiogenesis deceleration during the early stage of healing, impedes bone defect healing. These results demonstrate that OD‐BMSCs could offer intrinsic inhibitory signals on sprouting angiogenesis and the appropriate emergence timing of these signals is crucial to maintain vasculature homeostasis during bone repairing. These results provide insight into the complex interaction between osteogenesis–angiogenesis coupling and suggest the potential therapeutic application of IGFBP7 in regulating vascular homeostasis.